Laboratory investigation of vitamin C - Lewis, Anthony C.; Belt, Simon (The University of Hull)
This is a laboratory-based investigation of the Vitamin C content of foodstuffs after different cooking treatments. As described, the experiment illustrates the influence of cooking methods on the apparent Vitamin C content of green peppers. Analysis of Vitamin C is achieved by wet chemical methods or by HPLC.